The 2011 edition of the moot court competition on the International Criminal Court in the spanish language (2011)
On 10 June 2011 the Final Round of the 2011 edition of the Moot Court Competition on the International Criminal Court in the Spanish Language (the ‘ICC Moot Court Competition’) was held at the seat of the International Criminal Court (ICC) in The Hague. Judge Silvia Fernández de Gurmendi from Argentina presided over a panel of three ICC judges including herself, Judge Sylvia Steiner from Brazil and Judge Elizabeth Odio Benito from Costa Rica. Students from the universities Carlos III (Spain), del Rosario (Colombia) and Sergio Arboleda (Colombia) presented oral arguments in the roles of Prosecution, Representatives of State and Regal Representatives of Victims in a fictitious case written by Héctor Olásolo, Professor of International Criminal law and International Criminal Procedure at Utrecht University, and his team at the Utrecht School of Law Clinical Programme on Conflict, Human Rights and International Justice. This was the first hearing ever held in the Spanish language at the ICC since its establishment. It was also the first hearing ever held in the Spanish language before any international criminal court or tribunal.